Visibility of Pulmonary Valve and Pulmonary Regurgitation on Intracardiac Echocardiography in Adult Patients with Tetralogy of Fallot - Ichiro Sakamoto; Kenichiro Yamamura; Ayako Ishikita; Kisho Ohtani; Shintaro Umemoto; Hidetaka Kaku; Yuzo Yamasaki; Kohtaro Abe; Tomomi Ide; Hiroyuki Tsutsui (Journal of Cardiovascular Development and Disease, 2023)
Pulmonary regurgitation (PR) is a risk factor for sudden cardiac death in adult patients with repaired tetralogy of Fallot (TOF). However, transthoracic echocardiography (TTE) cannot fully visualize the pulmonary valve (PV) and PR. We investigated whether intracardiac echocardiography (ICE) could visualize the PV and PR better than TTE. Thirty adult patients with TOF (mean age 33 ± 15 years) scheduled for cardiac catheterization underwent ICE. The visualization of PV and the severity of PR were classified into three grades. ICE depicted the PV better than TTE (ICE vs. TTE: not visualized, partially visualized, and fully visualized: n = 1 [3%], n = 13 [43%], and n = 16 [53%] vs. n = 14 [47%], n = 13 [43%], and n = 3 [10%], p < 0.001). Especially in patients after pulmonary valve replacement (PVR), the PV was more fully visualized by ICE. The assessment of PR by TTE underestimated the severity of PR in comparison to cardiac magnetic resonance imaging (MRI) (severe PR: 8 [28%] vs. 22 [76%], p = 0.004), while there was no discrepancy between the results of ICE and MRI (21 [72%] vs. 22 [76%], p = 1.000). In comparison to TTE, ICE can safely provide better visualization of the PV and PR in adults with TOF, especially in patients who have undergone PVR.